"The Return of the Soul": Psychology, Theology and Soul‐Making. (19th January 2016) - Tyler, Peter
Abstract: Psychologists have recently once again started using "soul‐language" in their anthropological investigations. This paper will explore some of the attempts to "re‐soul" psychology over the past few decades, especially in the work of Bruno Bettleheim, Otto Rank and James Hillman. Having explored the strengths and weaknesses of these positions the paper ends with an account of the self taken from the work of St Teresa Benedicta a Cruce (Edith Stein) which, it argues, enables the Christian Trinitarian perspective to resolve tensions inherent in the other psychological models.